The Value of Remote Work: A Correspondence Experiment on Tutors - Sofoklis Goulas (Institute of Labor Economics (IZA), 2025)
This study explores the preference for remote work by sending thousands of randomized messages to tutors advertising on an online platform across Greece. The messages requested either in-person or online tutoring. Requests for online lessons were roughly 50 percent more likely to receive a callback (10.7 vs. 7.3 percent). Female tutors, STEM tutors, and those in high-competition areas showed stronger preferences for online lessons. Tutors favoring remote work also demanded higher premiums for in-person sessions. Survey findings suggest that online tutoring aligns with higher job satisfaction, more employment opportunities, improved instructional effectiveness, and increased tutoring hours.
Keywords: J2; J3; J4; J6; C93; 330; remote work; wages; in-person wage premium; online learning; tutoring; experiment